VERSUS: Heritage for Tomorrow Vernacular Knowledge for Sustainable Architecture - Correia, Mariana; DIPASQUALE, LETIZIA; Mecca, Saverio (Firenze University Press, 2014)
Vernacular architecture represents a great resource that has considerable potential to define principles for sustainable design and contemporary architecture. This publication is the result of an overall aim to produce a valuable tool for analysis regarding vernacular heritage through different assessments, in order to define principles to consider for sustainable development. This was possible through a comprehensive reflection on the principles established and the strategies to recognise in different world contexts. The present publication was the result of an in-depth approach by 46 authors from 12 countries, concerned with the analysis and critical assessment of vernacular heritage and its sustainable perspective. The book presents 8 chapters addressing operational definitions and synopses advances, regarding the main areas of vernacular heritage contribution to sustainable architecture. It also presents 15 chapters and 53 case studies of vernacular and contemporary approaches in all the 5 continents, regarding urban, architectural, technical and constructive strategies and solutions. VERSUS, HERITAGE FOR TOMORROW: Vernacular Knowledge for Sustainable Architecture is the result of a common effort undertaken by the partners ESG | Escola Superior Gallaecia, Portugal, as Project leader; CRAterre | École Nationale Supérieure d'Architecture de Grenoble, France; DIDA | Università degli Studi di Firenze, Italy; DICAAR | Università degli Studi di Cagliari, Italy; and UPV | Universitat Politècnica de València, Spain. This is the final outcome of VerSus, an European project developed from 2012 to 2014, in the framework of the Culture 2007-2013 programme.